Supervision of Financial Conglomerates : The Case of Chile - Stephanou, Constantinos (World Bank, Washington, DC, 2012)
The author describes the presence of financial conglomerates and assesses the extent to which the risks they introduce to the Chilean financial system are mitigated by existing oversight arrangements (and at what cost). In particular, he questions whether the current silo-based supervisory framework, which has served the system fairly well until now, can continue unchanged given growing inter-linkages in the financial system. The author proposes a high-level short- and medium-term supervisory reform agenda that addresses identified vulnerabilities relating to financial conglomerates and continues the migration from a rules-oriented to a risk-based supervisory approach that has gradually been taking place in Chile in recent years.